PENGGUNAAN TEKNOLOGI DALAM PENDIDIKAN TANTANGAN GURU PADA ABAD 21 - Siswanti, Linda (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
One of the challenges of teachers in the 21stcentury is the use of technology in education. In general, experts argue that multiple-faced technology. On the one hand, technology provides many conveniences and benefits, so there are teachers who rely on the use of technology in education. However, on the other hand, technology can also have a negative impact on education. The use of scaffolding in the form of technology can eliminate the essence of education. Therefore, the use of technology as an educational support must be accompanied by an awareness to continue to accommodate and maintain that essence. The essence of education is not only about transfers knowledge, but also gives exemplary, inculcates good values, fosters character, fosters potential "uniqueness" of each student, gives motivation, and looks like in the form of other "hidden curriculum". Such a thing cannot be achieved by relying solely on technological support, but requires human-intersubjective interaction between teacher-student, between students, and between teachers and students with learning resources. Therefore, a thought about "the use of technological support in learning, however still giving "the essence" of education ", it is necessary with awareness carried out by the teacher. If not, the accumulation of long-term negative impacts from the use of technological support in education will be very large. We might actually lose the "important thing" in education. The phenomenon of reductionism in education, which relies on a material summary book plus practice questions that seem to have become symptomatic and entrenched, perhaps shows that the essence of education has increasingly disappeared.